2021
DOI: 10.1155/2021/5410218
|View full text |Cite|
|
Sign up to set email alerts
|

Multimedia Archives: New Digital Filters to Correct Equalization Errors on Digitized Audio Tapes

Abstract: Multimedia archives face the problem of obsolescing and degrading analogue media (e.g., speech and music recordings and video art). In response, researchers in the field have recently begun studying ad hoc tools for the preservation and access of historical analogue documents. This paper investigates the active preservation process of audio tape recordings, specifically focusing on possible means for compensating equalization errors introduced in the digitization process. If the accuracy of corrective equaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…e algorithm attempts to find similar image blocks from the image data set by using feature matching and reconstruct the original image by using similar image blocks. Although the reconstruction effect obtained by this algorithm is not ideal, the method of using local features to find the correlation between image blocks is worthy of reference [4]. Cao and others proposed a cloud based distributed coding algorithm.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…e algorithm attempts to find similar image blocks from the image data set by using feature matching and reconstruct the original image by using similar image blocks. Although the reconstruction effect obtained by this algorithm is not ideal, the method of using local features to find the correlation between image blocks is worthy of reference [4]. Cao and others proposed a cloud based distributed coding algorithm.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When calculating the contrast masking weighting factor of the digital multimedia video image, first divide the digital multimedia video image into three regions, namely, smooth region, texture region, and edge region. Weight different regions of the image according to formula (4).…”
Section: Fault Tolerant Digital Video Transmission Systemmentioning
confidence: 99%
“…is is particularly beneficial for multimedia archival information resources, which are traditionally stored in a structured manner because they exist mainly in text format. With the upgrading of hardware equipment and the development of modern Internet technologies, archival information resources exist in a variety of forms, including text, images, videos, or structured records [1,13] such as lists and tables, which can also contain unstructured data.…”
Section: Data Miningmentioning
confidence: 99%
“…With the rapid evolution of data-related technology in today's Internet era, data have become increasingly important. In the past, traditional data held by di erent departments often showed a chimney-type silo e ect, with great correlation value between each other but could not be fully utilized, especially in archival information resources [1]. e development and advancement of information technology (IT) have led to the deep mining of archival information, making the various elements of archival information management form intrinsic links and fully realizing the sharing of archival information resources [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In the article titled "Multimedia Archives: New Digital Filters to Correct Equalization Errors on Digitized Audio Tapes" [1], the authors identified an error in the presentation of equation ( 1) and its explanation with regard to time's unit which was expressed in microseconds in Section 2.2. Hence, corrected equation (1) and its corresponding explanation are found as follows:…”
mentioning
confidence: 99%